2014
DOI: 10.1007/s12633-014-9233-z
|View full text |Cite
|
Sign up to set email alerts
|

Polycondensation of Diethoxydimethylsilane in Active Medium

Abstract: Polycondensation of diethoxydimethylsilane (DEDMS) in an active medium containing an excess of acetic acid was studied. It has been shown that the process selectivity could be well managed only if water was generated in the reaction mixture. We have found that both linear oligomers and cyclosiloxanes could be obtained with high selectivity and 80 % yield at least under conditions of the active medium. Further condensation of the linear oligomers led to the formation of α, ω-dihydroxypolydimethylsiloxanes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…However, this method is less suitable for obtaining a well-defined structure, amenable to regulation, and is accompanied by the need for additional stages to obtain high-molecular structures. One of the important exclusions to the general rule is the synthesis of telechelics in an active medium followed by post-condensation using catalysts [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, this method is less suitable for obtaining a well-defined structure, amenable to regulation, and is accompanied by the need for additional stages to obtain high-molecular structures. One of the important exclusions to the general rule is the synthesis of telechelics in an active medium followed by post-condensation using catalysts [37].…”
Section: Introductionmentioning
confidence: 99%
“…The azido group was incorporated into the monomer structure by the technique reported previously . The hydrolytic condensation of functional alkoxy monomers with azidopropyl-functional groups was carried out in an active medium (30% solution in acetic acid) until complete disappearance of alkoxy groups in the 1 H NMR spectra. …”
Section: Results and Discussionmentioning
confidence: 99%
“…10 These studies and related work by Muzafarov demonstrated that siloxane bond formation can be elicited by acidic transesterification processes. 11 As noted, the reaction is slow in the absence of strong acids. The above processes described typically utilized excess acetic acid as an active medium.…”
Section: ■ Introductionmentioning
confidence: 91%